GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 153 species occurrences available in GBIF matching the query: TaxonKey: Ipomoea aquatica Forsk. Country: Indonesia. The dataset includes 153 records from 7 constituent datasets: 72 records from A global database for the distributions of crop wild relatives. 63 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 1 records from NMNH Extant Specimen and Observation Records. 1 records from United States National Plant Germplasm System Collection. 13 records from The System-wide Information Network for Genetic Resources (SINGER). 1 records from Bernice P. Bishop Museum. 2 records from Royal Botanic Gardens, Kew - Herbarium Specimens. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences